The Effectiveness of Contextual Play-Based Learning in Enhancing Language Skills of Early Childhood Learners with Learning Difficulties - Misna, Misna; Pamungkas, Bayu (Papanda Publisher, 2025)
This study investigates the effectiveness of contextual Play-Based Learning in improving the expressive language skills of early childhood learners with identified learning difficulties. The research was conducted as a classroom action study at TK Negeri 1 Sandaran, East Kalimantan, involving 13 children aged 5–6 years, five of whom were diagnosed with language development delays. The intervention was conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. Instructional activities were designed around the theme “Animals,” using role-play, guessing games, simulations, and peer collaboration to stimulate verbal engagement. Data were collected through structured observations, performance-based tasks, and anecdotal records, and analyzed descriptively. Results showed a progressive improvement in children’s expressive language abilities. In the pre-intervention phase, most participants were categorized as “Not Yet Developed.” Following Cycle I, all five targeted children reached the “Emerging Development” stage, while Cycle II saw 80% achieve the “Expected Development” level. Improvements were observed in vocabulary use, sentence construction, and peer interactions. The use of familiar, contextual themes combined with teacher scaffolding and strategic peer grouping significantly contributed to the success of the intervention. These findings underscore the potential of contextual Play-Based Learning as an inclusive instructional approach to support language development in early learners with verbal challenges. The study also emphasizes the importance of ongoing assessment, reflective teaching, and instructional adaptation to meet the diverse needs of learners.